2011
DOI: 10.3917/reco.623.0471
|View full text |Cite
|
Sign up to set email alerts
|

When are Central Bankers Removed?

Abstract: Quand les banquiers centraux sont-ils destitués ? Cet article montre que la probabilité de remplacement d’un gouverneur de banque centrale est positivement liée à la part du mandat déjà effectuée, aux crises bancaires et monétaires, aux élections, aux réformes des statuts des banques centrales, ainsi qu’à l’inflation. En outre, il est montré que les résultats dépendent de la régularité ou de l’irrégularité du remplacement, et de ce qu’il intervient avant ou après le terme de la durée légale du mandat. JEL Code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…With regards to the institutional commitments of a central bank, Muhammad A. Hayat and Étienne Farvaque (2011) estimated the probability of removal of a central banker in 103 countries all over the world. The main conclusion is that "'central bankers' removals are related to banking and currency crises, to elections and the change in the strength of democracy, and to inflation performance and globalization" (Hayat and Farvaque 2011).…”
Section: Trust In Institutions and Economic Outcomes: The Literature mentioning
confidence: 99%
“…With regards to the institutional commitments of a central bank, Muhammad A. Hayat and Étienne Farvaque (2011) estimated the probability of removal of a central banker in 103 countries all over the world. The main conclusion is that "'central bankers' removals are related to banking and currency crises, to elections and the change in the strength of democracy, and to inflation performance and globalization" (Hayat and Farvaque 2011).…”
Section: Trust In Institutions and Economic Outcomes: The Literature mentioning
confidence: 99%
“…Among others, , 2006Rodrik & Wacziarg, 2005) analyze the relation between democracy and inequality inside the framework of game theory: it is the redistributive threat by part of the population that brings 11 A study about the institutional commitments of a Central Bank may be found in Hayat et al (2011), estimating the probability of removal of a central banker in 103 countries worldwide. The main conclusion is that "central bankers' removals are related to banking and currency crises, to elections and the change in the strength of democracy, and to inflation performance and globalization" (Hayat et al, 2011 p.17) about a democratic equilibrium 12 .…”
Section: Trust and Economic Performancementioning
confidence: 99%
“…As the greater "illusion of precision"-type overconfidence lowers the one-period loss value as in (9), an increase in γ actually raises the benefit of keeping an incumbent central banker.…”
Section: Comparative Statics Analysismentioning
confidence: 97%
“…This study contributes by formally modeling the behavioral biases and deriving their consequences. It not only shows how the impacts of such overconfidence proceed through the whole macro-economy, but it also helps to understand an empirical puzzle, as central bankers, even though their institutions tend to become more similar (Crowe and Meade, 2007), still have different term lengths in their mandates and actual turnover rates (Hayat and Farvaque, 2011, Dreher et al, 2008, 2010.…”
Section: Introductionmentioning
confidence: 99%